2020
DOI: 10.1590/1980-0037.2020v22e70184
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the small-sided games in volleyball: an ecological approach

Abstract: The aim of the present study was to compare the tactical and technical behavior of beginner players in volleyball side-out between four distinct situations of reduced games with different area/player ratios: 4.5 m2 (3.0 m x 3.0 m), 8.0 m2 (4.0 m x 4.0 m), 10.58 m2 (4.6 m x 4.6 m), and 13.52 m2 (5.2 m x 5.2 m). We analyzed 76 games played by 16 players with a mean age of 12.2 ± 0.5 years and experience of 1.2 ± 0.8 years of practice. Tactical and technical behavior was analyzed using an adaptation of the Game P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The reason for the changes in Experimental Tournament 2 were the result of the combined impact of the limitations on the serve that were implemented (jump serve was not allowed and limit of two serves per player) and the changes in the net height and court size. Previous studies showed that a reduction of the court size increases the efficacy of the actions, except for the serve (Ronglan and Grydeland, 2006 ; Rocha et al, 2020a , b ; Rodrigues et al, 2022 ). At the psychological level, none of the experimental tournaments involved changes regarding players' individual or collective self-efficacy, perceived enjoyment, or perceived satisfaction with regard to the Control Tournament.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reason for the changes in Experimental Tournament 2 were the result of the combined impact of the limitations on the serve that were implemented (jump serve was not allowed and limit of two serves per player) and the changes in the net height and court size. Previous studies showed that a reduction of the court size increases the efficacy of the actions, except for the serve (Ronglan and Grydeland, 2006 ; Rocha et al, 2020a , b ; Rodrigues et al, 2022 ). At the psychological level, none of the experimental tournaments involved changes regarding players' individual or collective self-efficacy, perceived enjoyment, or perceived satisfaction with regard to the Control Tournament.…”
Section: Discussionmentioning
confidence: 97%
“…The reduction of the court area limits the ball trajectories, reduces ball speed, and increases the chances of intercepting the ball (Ronglan and Grydeland, 2006 ; Rodrigues et al, 2022 ). The specific effect of court manipulation changes for each court size (Rocha et al, 2020a , b ; Rodrigues et al, 2022 ). The changes of the court size are influenced by the number of players: m 2 per player (Halouani et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…information, where the learner performs the self-evaluation process to find out what the wrong performance is and correct it and enhance the correct performance by referring to the mental maps hanging in front of him that the teacher prepares in advance whereas Abdel Wahab stressed that mental maps (used to identify the main and sub-ideas supporting them, and the details of these ideas, and are also used for division, classification and grouping in the form of categories or groups, where the main idea is written at the top of the line, and the sub-ideas are written below, and the bottom of the classification branches are written Specific details for each branch, and multiple subsections can be made (Bieleke et al, 2019;Rocha et al, 2020). This is in contrast to the method used by the subject teacher when teaching the control group in which he was only interested in the educational material, i.e.…”
Section: Volume --| Issue -| 2022 |mentioning
confidence: 99%
“…With this assessment mechanism we are able to code and observe performance behaviors that demonstrate the ability to solve tactical problems in games by making decisions, moving appropriately, and executing skills [103,104]. These tools are flexible in their content (i.e., they can be adapted over time) and can be applied to real game contexts (or to an analytical situation) [103,105].…”
Section: Assessment: From a Formality To A Relevant Educational Toolmentioning
confidence: 99%